VD_FINDINFO Décision / 2021 / 219 vom 12. Mai 2021 - VD Tribunal cantonal (2021)
SUREXPERTISE, ADMISSION DE LA DEMANDE, EXPERTISE, COMPLÉMENT | 184 al. 3 CPP (CH), 189 CPP (CH), 393 al. 1 let. a CPP (CH)